Verzeichnis der im Deutschen Entomologischen Institut laufend gehaltenen Zeitschriften. - Köppen, Herbert (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The present list gives a survey of all journals currently received by Deutsches Entomologisches Institut.